Investigations of physical mechanisms of metal-insulator transition in highly strained n-Si and n-Ge crystals - Budzulyak, S.I.; Ermakov, V.M.; Kyjak, B.R.; Kolomoets, V.V.; Machulin, V.F.; Novoselets, M.K.; Panasjuk, L.I.; Sus', B.B.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Analysis of experimental results on transport phenomena is presented for highly uniaxially strained silicon and germanium crystals heavily doped by shallow donors. Possible mechanisms of the strain induced metal-insulator (MI) transition determined by peculiarities of the c-band energy spectrum transformation in n-Si and n-Ge are discussed. The main statements of the effective mass-donor concept for hydrogen-like impurities in monocrystalline semiconductors were verified.